2022
DOI: 10.3389/fimmu.2022.854312
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 and FOXO3 Cooperatively Regulate Innate Lymphoid Cell Development

Abstract: Natural killer (NK) cells play roles in viral clearance and early surveillance against malignant transformation, yet our knowledge of the underlying mechanisms controlling their development and functions remain incomplete. To reveal cell fate-determining pathways in NK cell progenitors (NKP), we utilized an unbiased approach and generated comprehensive gene expression profiles of NK cell progenitors. We found that the NK cell program was gradually established in the CLP to preNKP and preNKP to rNKP transitions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Any modulation of this route by interference with FOXO1 may therefore modulate chemosensitivity of CRC and present a novel target for treatment. A similar argument applies to the differentiation of NK cells, as FOXO1 and FOXO3 are necessary for normal development of the NK lineage and innate lymphoid cells [167] by modifying the expression of IL-15Rβ. Disrupting FOXO1/3 may have widespread implications for immune system function.…”
Section: Foxo1mentioning
confidence: 88%
“…Any modulation of this route by interference with FOXO1 may therefore modulate chemosensitivity of CRC and present a novel target for treatment. A similar argument applies to the differentiation of NK cells, as FOXO1 and FOXO3 are necessary for normal development of the NK lineage and innate lymphoid cells [167] by modifying the expression of IL-15Rβ. Disrupting FOXO1/3 may have widespread implications for immune system function.…”
Section: Foxo1mentioning
confidence: 88%
“…However, we did not observe a significant change in the cell number of ILC3s in Foxo1 -deficient mice, indicating a different regulatory mechanism mediated by FOXO1 in ILC3s. Luu et al found that ILC3 numbers were decreased in BM and thymus, and in contrast, NKp46 − ILC3s were increased in spleen of Foxo1,3 ΔVav mice compared with WT mice ( Luu et al, 2022 ). By using Vav-Cre, Foxo1 gene was depleted in all hematopoietic cells, including the progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al reported that FoxO1 is dispensable for NK cell development and that inactivation of FoxO1 is required for T-bet expression [ 94 ]. Furthermore, Luu et al reported that the combined loss of FoxO1 and FoxO3 caused specific changes in the composition of noncytotoxic innate lymphoid cell subsets in the BM, thymus, and spleen [ 95 ]. They also revealed that FoxO transcription factors ensure proper NK cell development at various lineage commitment stages by orchestrating distinct molecular mechanisms.…”
Section: Function Of the Foxo Transcription Factors In Immune Cellsmentioning
confidence: 99%